The Effect Of Understanding Of Local Government Accounting Systems And Human Resources Competence On The Performance Of Financial Managers With Welfare Benefits As A Moderation Variable - Manurung, Clessy Cristine Putri; Aloysius Harry Mukti (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aims to determine the effect of understanding the local government accounting system and human resource competence on the performance of financial managers with welfare benefits as a moderating variable at BPKAD (Regional Financial and Asset Management Agency) in Bekasi City. This research is a quantitative study. Data analysis was carried out using the Partial Least Square-Structural EM model through SmartPLS 3.0 software. With a causal research approach Primary data collection was carried out by distributing questionnaires to all employees at BPKAD in Bekasi City. The analysis of this research explain that (1) Understanding of local government accounting systems does not affect the performance of financial managers; (2) Human resource competence has a positive effect on the performance of financial managers; (3) Welfare allowances do not moderate the influence of the relationship between the understanding of the local government accounting system and the performance of financial managers; (4) Welfare allowances do not moderate the effect on the relationship of human resource competence on the performance of financial managers.